Acheulean Diversity in Britain (MIS 15-MIS11): From the Standardization to the Regionalization of Technology - García-Medrano, Paula; Shipton, Ceri; White, Mark; Ashton, Nick (Frontiers in Earth Science, 2022)
The appearance of the Acheulean and the production of new bifacial tools marked a revolution in human behavior. The use of longer and complex operative chains, with centripetal and recurrent knapping, adapted to different raw materials, created long useful edges, converging in a functional distal end. How and why these handaxes vary has been the subject of intense debates. Britain provides a clearly defined region at the edge of the hominin occupied world for discussing variation in Acheulean assemblages. The environmental changes from MIS 15 to MIS 11 are significant in understanding population change, with probable breaks in evidence during MIS 14 and MIS 12, followed by several sites during the long stable climate of MIS11c. In this latter period, different Acheulean technological expressions appear to coexist in Britain. This paper draws together different studies, combining technology and geometric morphometrics to analyze handaxes from six British sites: Brandon Fields, Boxgrove (Q1B), High Lodge, Hitchin, Swanscombe (UMG), and Elveden. Compared to the earlier Acheulean of MIS 15, the assemblages of MIS 13 show increased standardization and the use of soft hammer percussion for thinning mid-sections and butts of tools, or sharpening tips through tranchet removals. Although there is regional population discontinuity through MIS12 there is no evidence of a marked change in technology after this glacial period. Rather, there is a development towards more intense shaping with the same underlying techniques, but with flexibility in imposed handaxe form. From MIS11 there appear to be distinctive localized traditions of manufacture, which suggest that a recognition of place and territories had developed by this time. These are expressed over medium time-scales of several thousand years and have significance for how we view cultural expression and transmission.